Influence of Civil Servants Competency to Productivity: Review of PanRB Ministerial Regulation 01 Of 2023 - Lilis Aslihah Rakhman; Naf'an Torihoran; Yayat Supriyadi (AMCA Journal of Community Development, 2024)
This study aims to obtain answers regarding the significance or absence of the relationship between equalization of civil servants competency and productivity. In addition, this study is also to find what methods are used in obtaining a complete and accurate description of the equalization of civil servants competency to productivity. This research is a study that uses correlation studies, in this way the research conducted can find out how much the contribution of equalization of civil servants competency  (independent variables) to productivity (dependent variables). In accordance with these variables, the instruments made are instruments to measure the equalization of civil servants competency and productivity instruments of civil servants. These instruments are set out in the form of questionnaires or statements with scaled alternative answers to opinions or attitudes. On this basis, the measurement scale uses the Likert Scale. This study establishes a causal relationship between several variables, namely: civil servants competency, perceived organizational support, social relationships in the workplace, response to change, willingness to change and performance of civil servants. Civil Servants competency variables refer to Competencies: (Skill, Knowledge, Atittude). The productivity variable refers to Civil Servant's perception of the extent to which the organization values donations, provides support, and cares about employee well-being. Productivity is influenced by factors: (1) Quality and physical ability of employees; (2) Supporting Facilities; (3) Satisfactory facilities. The benefits of this research are, it is expected to be a contribution of thought in the field of Human Resource Management and social sciences in general. While practically, this research is expected to be useful for decision making in the field of human resource development by utilizing the findings of the results of this research.